117k views
1 vote
F(x) = 4x – 10
g(x) = -8x2 + 6x – 10
Find: f(x) · g(x)

User CorribView
by
6.3k points

1 Answer

4 votes

Answer: f(x) · g(x)=-32x³+104x²-100x+100

Explanation:

Since we are given f(x) and g(x), all we have to do is multiply them together.

f(x) · g(x)=(4x-10)(-8x²+6x-10) [distribute by FOIL]

f(x) · g(x)=-32x³+24x²-40x+80x²-60x+100 [combine like terms]

f(x) · g(x)=-32x³+104x²-100x+100

Now, we have multiplied them together, we have f(x) · g(x)=-32x³+104x²-100x+100.

User Hbruce
by
6.7k points